PERLINDUNGAN KONSUMEN DALAM TRANSAKSI E-COMMERCE DENGAN MENGGUNAKAN REKENING BERSAMA (Commerce Law, 2024)
ABSTRACTThis research aims to examine consumer protection in cases where an escrow service provider commits a breach of contract and to understand the legal liability towards consumers in the event of a loss. The type of research used is normative legal research. The study finds that in an agreement between the consumer, the business actor, and the service provider, certain conditions must be met for the agreement to be valid. These conditions include mutual consent, legal capacity to form a contract, a clear subject matter, and a lawful cause. Consumer protection in cases of breach of contract can be found in Article 7 of Law Number 8 of 1999, which requires compensation, indemnification, and/or replacement for losses due to the use of goods and/or services traded, and requires compensation, indemnification, and/or replacement if the goods and/or services received or used do not comply with the agreement. Additionally, compensation payments are regulated by Articles 1244 and 1245 of the Indonesian Civil Code. According to Article 1244, if it cannot be proven that the breach of contract was due to an unforeseeable event, the escrow service (Blackpanda) is obligated to compensate for the losses arising from the transaction. However, Article 1245 states that if it can be proven that the breach occurred due to a compelling situation beyond the control of the escrow service, the service provider is exempt from compensating for the breach.Keywords: Transactions, E-Commerce, Escrow Accounts
Keywords: Transactions; E-commerce; Escrow Accounts